Analysis of The Effect Public Facilities on The Level of Tourist Satisfaction in Tenganan Pegringsingan Village, Karangasem District - Paramarta, Pande Made Ari Ananta; Rusadi, Ni Wayan Purnami (JURNAL MANAJEMEN AGRIBISNIS, 2024)
Tenganan Village, Manggis District, Karangasem Regency is one of the tourist villages in Bali Province. Tenganan Village consists of 1,2013 families with a population of 4,627 people. Tenganan Pegringsingan Village has had a decreased level of visits. The highest number of visits occurred in 2010, namely 57,848 people and the lowest in 2018 was 28,468 people. This study aims to determine the effect of public facilities on the level of tourist satisfaction in the Tourism Village of Tenganan Pegringsingan, Karangasem Regency. The results of this study indicate the general facilities that affect the increase in tourist satisfaction in Tenganan Village, which causes the highest increase is the parking lot of 7.99 percent. There are two variables that cause a decrease in satisfaction which of course needs attention, namely restaurant and lodging facilities. The Karangasem Regency Government as the regional government making the regulations must pay attention to the layout of tourism users in the Tenganan Village area and the surrounding villages so that the authenticity of Tenganan Village can be maintained.